The Effect Of Exchange Rate, Interest Rates, And Foreign Direct Investment On JCI For The Consumer Goods Industry Sector With Profitability As A Moderation Variable (2019–2024 Period) - Muhammad Taufiq; Ronny Malavia Mardani; Mohammad Bastom (UNIVED Press, 2026)
This study aims to analyze the effect of exchange rates, interest rates, and Foreign Direct Investment (FDI) on the Composite Stock Price Index (CSPI) in the consumer goods industry sector and to examine the role of profitability as a moderating variable. This study employed a quantitative approach using secondary data obtained from the Indonesia Stock Exchange, Bank Indonesia, Statistics Indonesia, and the Investment Coordinating Board during the 2019–2024 period. The sample was determined using a purposive sampling method, resulting in 25 food and beverage sub-sector companies with a total of 150 observations. The analytical techniques used were multiple linear regression and Moderated Regression Analysis (MRA). The results show that exchange rates have a positive and significant effect on the CSPI, while interest rates and FDI have a negative and significant effect on the CSPI. Simultaneously, all independent variables significantly affect the CSPI. Meanwhile, profitability is unable to moderate the effect of exchange rates, interest rates, and FDI on the CSPI, indicating that the influence of macroeconomic variables on the CSPI is direct. These findings suggest that movements in the CSPI of the consumer goods industry sector are more dominantly influenced by external macroeconomic factors than by internal company factors. This study strengthens the relevance of Arbitrage Pricing Theory (APT) in explaining the relationship between macroeconomic factors and the capital market and provides implications for investors, companies, and policymakers in understanding stock market dynamics in Indonesia.